Etika Komunikasi Bagi Pengguna Media Sosial Menurut Al-Qur’an - Anggraini, Novi (Journal of Comprehensive Islamic Studies, 2024)
Social media has become the main platform for communicating and interacting in modern life. However, irresponsible use can lead to negative consequences such as slander, violations and misunderstandings. Therefore, it is important to understand the communication ethics indicated by the Al-Qur'an as a moral guideline in using social media. This article aims to outline the principles of communication ethics contained in the Al-Qur'an that can be applied by social media users. The research used is qualitative research of the Library Research type using the thematic interpretation method, collecting verses on communication ethics. The results of this research found that the communication ethics recommended according to the Al-Qur'an for social media users are closely related to the characteristics of social media users. Rasulullah SAW who is a role model for us, namely Siddiq, Amanah, Tabligh and Fatonah. Thus, these findings provide an overview of how the Al-Qur'an can be a source of inspiration for developing responsible and ethical communication behavior in the digital environment. Media sosial telah menjadi platform utama untuk berkomunikasi dan berinteraksi dalam kehidupan modern. Namun, penggunaan yang tidak bertanggung jawab dapat mengarah pada konsekuensi negatif seperti fitnah, penghinaan, dan kesalahpahaman. Oleh karena itu, penting untuk memahami etika komunikasi yang ditunjukkan oleh Al-Qur'an sebagai panduan moral dalam bermedia sosial. Artikel ini bertujuan untuk menganalisis prinsip-prinsip etika komunikasi yang terkandung dalam Al-Qur'an yang dapat diterapkan oleh pengguna media sosial. Penelitian yang digunakan adalah penelitian kualitatif jenis Library Research dengan menggunakan metode tafsir tematik, mengumpulkan ayat-ayat etika komunikasi.Hasil penelitian ini menemukan bahwasanya mengenai etika komunikasi yang dianjurkan menurut Al-Qur’an terhadap para pengguna media sosial, erat kaitanya dengan sifat-sifat Rasulullah SAW yang menjadi tauladan bagi kita, yaitu Shiddiq, Amanah, Tabligh dan Fatonah. Dengan demikian, hasil temuan ini memberikan pandangan tentang bagaimana Al-Qur'an dapat menjadi sumber inspirasi untuk mengembangkan perilaku komunikasi yang bertanggung jawab dan etis dalam lingkungan digital.